China's trade performance and its impacts on Asian economies - Sari, Dyah Wulan (The Philippine Review of Economics, 2006)
In 2001, China joined the World Trade Organization (WTO), and its economy has since opened up through domestic reform. The Chinese government has also since tried enthusiastically to lure a lot of investors- and succeeded. As a consequence, China's exports have boomed, and China has become a most enthusiastic importer. This development has brought great opportunities for the Asian economy, with interregional trade being the principal contributor to China's steady export growth. Chinese imports have been more accurately termed "imports from the integrated Asian regional economy".